Glucose tolerance in patients with abnormal endometrial bleeding during and after the climacteric - Benjamin, Fred (Department of Pathology, 2020)
Two thousand years elapsed before man could unravel several of the problems and implications of disturbed glucose tolerance. As far back as 30 years B.C. gross manifestations of the disease now known as Diabetes Mellitus were recognized. Despite great advances, however, there is much that is still unknown. The history of many a malady begins with the observation of the illness in its most grotesque form. As medical science gathers more and more knowledge the less severe symptoms and signs come to be recognized. Gradually special tests are evolved, by means of which the disorder can be diagnosed inits earliest stages. And thereafter, the tendency to develop the condition is seen before it becomes manifest. The long history of disturbed glucose tolerance follows this pattern. Many centuries have passed in the gradual evolvement of the various stages. With the passing of the years improved diagnostic methods were discovered, so that mild rooms of the disorder could be detected. In the past few decades the concept of mildly impaired glucose and "pre-diabetes" has been formulated. One of the most interesting of recent developments, for example, has been the conclusion that the birth of overlarge babies may be a sign of predisposition to this metabolic disturbance.